Internalization of Multicultural-Based Religious Guidance in Building Religious Moderation in Lembang - Adiansyah Adiansyah; M. Fadhil Yarda Gafallo Fadhil Yarda Gafallo; Abdul Aziz Azis; M. Sufyan Tsauri Sufyan Tsauri (Fakultas Dakwah UIN Kiai Haji Achmad Siddiq Jember, 2023)
The existence of Islam emerged amidst the multicultural population of the Arab nation. Similar to the diversity that the Arab nation possesses, Indonesia is classified as a multicultural society, which means that it has cultural, ethnic, linguistic, and religious diversity. Each island has different cultures, ethnicities, languages, and even religions, making it a non-material wealth owned by the Indonesian nation. On the other hand, diversity can also become a potential conflict, thus requiring preventive efforts to avoid conflicts that can occur at any time, such as what happened in Lembang Village, Sanggau Ledo District. Researchers noted that there were at least two ethnic conflicts that occurred in late 1996 and 1999, which resulted in many casualties. Regardless of the conflicts that have occurred, currently, the community in Lembang Village is living with social, cultural, and religious stability, and it has been 24 years since any conflict was recorded. Through qualitative research, the researchers sought to explore how the internalization of multicultural-based religious guidance can build religious moderation in Lembang Village. As a result, the researchers found two patterns of da'wah that were applied. Firstly, emphasizing normative-contextual communication between three major Islamic organizations, namely Nahdlatul Ulama, Muhammadiyah, and Jama'ah Tabligh. Secondly, providing religious guidance that contains the material of aqidah, akhlaq, worship, and muamalah through the Majelis Taklim and TPQ institutions so that the people of Lembang Village can live harmoniously and move further away from the terminology of